The Transcriptional Program of Staphylococcus aureus Phage K Is Affected by a Host rpoC Mutation That Confers Phage K Resistance - Rohit Kongari; Melissa D. Ray; Susan M. Lehman; Roger D. Plaut; Deborah M. Hinton; Scott Stibitz (Viruses, 2024)
To better understand host–phage interactions and the genetic bases of phage resistance in a model system relevant to potential phage therapy, we isolated several spontaneous mutants of the USA300 S. aureus clinical isolate NRS384 that were resistant to phage K. Six of these had a single missense mutation in the host rpoC gene, which encodes the RNA polymerase β’ subunit. To examine the hypothesis that mutations in the host RNA polymerase affect the transcription of phage genes, we performed RNA-seq analysis on total RNA samples collected from NRS384 wild-type (WT) and rpoCG17D mutant cultures infected with phage K, at different timepoints after infection. Infection of the WT host led to a steady increase of phage transcription relative to the host. Our analysis allowed us to define 53 transcriptional units and to categorize genes based on their temporal expression patterns. Predicted promoter sequences defined by conserved −35, −10, and, in some cases, extended −10 elements, were found upstream of early and middle genes. However, in many cases, sequences upstream of late genes did not contain clear, complete, canonical promoter sequences, suggesting that factors in addition to host RNA polymerase are required for their expression. Infection of the rpoCG17D mutant host led to a transcriptional pattern that was similar to that of the WT at early timepoints. However, beginning at 20 min after infection, transcription of late genes (such as phage structural genes and host lysis genes) was severely reduced. Our data indicate that the rpoCG17D mutation prevents the expression of phage late genes, resulting in a failed infection cycle for phage K. In addition to illuminating the global transcriptional landscape of phage K throughout the infection cycle, this study will inform our investigations into the basis of phage K’s control of its transcriptional program as well as mechanisms of phage resistance.